The effects of assessment instruction and test anxiety on divergent components of creative problem-solving tasks - Prokofieva, Victoria; Fenouillet, Fabien; Romero, Margarida (Frontiers in Education, 2024)
This study looked at how an assessment instruction can influence divergent thinking components (DT) of creativity in a playful robotic problem solving task. We measured test anxiety (TA) and DT performance under assessment and non-assessment conditions in 122 secondary students. The aspects of DT showed a tendency to be impacted by assessment instruction. However, no correlation was found between TA and DT and no gender or age differences were observed. The results suggest that TA does not influence performance of the students involved in creative problem solving processes. Moreover, unlike studies reporting a negative impact that assessment can produce on performance in difficult tasks, we observe that under assessment conditions learners' performance was practically not impaired in playful creative problem solving tasks. We discuss these results in relation to game-based learning specificities. The assessment instruction in playful activities can be perceived as a positive challenge and even the students showing higher levels of test anxiety do not perceive it as a threat. Under non-assessment condition the learners show higher fluidity in the first occurrence of the task, but the originality turns to be impaired in the second trial. The finding of this study opens promising perspectives to the research on innovative forms of school assessment.